Corrosion Control of Electrolyzer, Anolyte Tank and Dechlorination Tower Tank of a Chlor-Alkali Plant by an Innovative Method - Kundu, Sazal Kumar (Journal of Chemical Engineering, 2010)
Brine purification process of GHCL did not meet the specification of electrolyzer in the context of excess hydroxide ion (OH-). The electrolyzer, anolyte tank and dechlorination tower tank faced serious corrosion. This paper describes an innovative method adopted to meet the electrolyzer's specification of excess OH-. This method consists of an innovative HCl dosing system added to purified brine tank. After adopting this method corrosion of electrolyzer, anolyte tank and dechlorination tower tank has been decreased in a noticeable rate. Also some chemical dosings have been reduced. Journal of Chemical Engineering Vol.ChE 24 2006 37-41